State and Community Participation in the Democratization Process in Indonesia - Bayu Karunia Putra; Krishno Hadi (International Journal of Education, Information Technology, and Others, 2022)
This article aims to determine the state and community participation in the democratization process in Indonesia. This topic is important and interesting, because it is mandatory to protect and care for the democratic system, bearing in mind that current developments in the state and society have raised various kinds of issues that must be answered, especially with regard to the democratic system in Indonesia. The research method used is the literature review method, in which sources and data are obtained through the Publish or Perish, SINTA, and Goggle Scholar databases. In this method, the researcher uses a descriptive qualitative approach, in which this method utilizes qualitative data and is described descriptively. Data collection techniques use literature review techniques carried out by researchers to collect valid, complete, and relevant information related to the topic of the problem which is the object of research. The data analysis technique used a literature review analysis technique, in which this research was conducted by reading literary sources to obtain the necessary data. The author finds that, with the existence of a democratic system, it can create a life of nation and state that is in accordance with the mandate of Pancasila and the 1945 Constitution.